DIAGNOSA PENYAKIT DIABETES DENGAN METODE FORWARD CHAINING - Sri Hardani (LPPM Nusa Mandiri, 2020)
Diabetes is a disease that causes many deaths. From year to year, the number of people with diabetes is increasing. If known earlier, sufferers can control their disease through medication, lifestyle changes, and eating patterns. With the technology that helps in diagnosing the disease, will help patients to find out the disease without having to see a doctor. By applying the forward chaining method that works by reading the facts that are then applied in the applicable rules, so as to produce a conclusion, the system reads the symptoms complained of by the patient to find out the type of diabetes suffered